2014
DOI: 10.5713/ajas.2013.13417
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of High Pressure Processing and Addition of Soy Sauce and Olive Oil on Safety and Quality Characteristics of Chicken Breast Meat

Abstract: This study was conducted to evaluate the combined effect of high pressure (HP) with the addition of soy sauce and/or olive oil on the quality and safety of chicken breast meats. Samples were cut into 100 g pieces and 10% (w/w) of soy sauce (SS), 10% (w/w) of olive oil (OO), and a mixture of both 5% of soy sauce and 5% olive oil (w/w) (SO) were pressurized into meat with high pressure at 300 or 600 MPa. Cooking loss was lower in OO samples than SS samples. With increased pressure to 600 MPa, the oleic acid cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 43 publications
3
20
0
Order By: Relevance
“…; Kruk et al . ). Generally, 500 MPa is the critical pressure that initiates lipid oxidation in chicken breast fillet (Orlien et al .…”
Section: Resultsmentioning
confidence: 97%
“…; Kruk et al . ). Generally, 500 MPa is the critical pressure that initiates lipid oxidation in chicken breast fillet (Orlien et al .…”
Section: Resultsmentioning
confidence: 97%
“…Kruk et al. () indicated that chicken breast meat with added olive oil treated by HPP at 300 MPa exhibited significantly reduced hardness.…”
Section: Food Texture Modification Technologiesmentioning
confidence: 99%
“…Briones-Labarca, Perez-Won, Zamarca, Aguilera-Radic, and Tabilo-Munizaga (2012), for example, reported that HPP-treated abalone exhibited a significant decrease in the fat content at all tested pressure/time combinations (500 MPa for 8 min or 550 MPa for 3 and 5 min). Kruk et al (2014) indicated that chicken breast meat with added olive oil treated by HPP at 300 MPa exhibited significantly reduced hardness.…”
Section: Textural Modification Of Meat and Meat Productsmentioning
confidence: 99%
“…Sorenson et al (2011) reported that HP could improve the eating quality of a chilled ready meal manufactured using a low-value beef cut, such as beef brisket. Recently, and Kruk et al (2014) reported that HP enabled the penetration of vegetable oils into beef loin changing the fat content, fatty acid composition, and sensory quality. However, HP processing may accelerate lipid oxidation and change the color of the meat (Kruk et al, 2011).…”
Section: Introductionmentioning
confidence: 99%